HubunganAntara Pola Asuh Orang Tua dengan Kemandirian Belajar Siswa Kelas V SD - Minasari Minasari; Abd Kadir; Latri Aras; Rahmawati Patta (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study is a quantitative study with a correlation design which aims to determine the relationship between parenting patterns and the learning independence of fifth grade students of SD Cluster III, Majaleng District, Wajo Regency. The population in this study were the fifth grade students of SD Cluster III, Majaleng District, Wajo Regency with 62 students. The data was collected by using a questionnaire. The data analysis technique was descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, it was found that the democratic type of parenting was the most widely used parenting category by parents, as many as 30 students with a percentage of 48.3, students' learning independence had an average of 94.43 and a percentage of 87.44. Based on the results of inferential statistical analysis, the t-valuecount(17.40382) is greater (>) the t-valuetable(9.48773) at the 5% significance level. Thus Ho is rejected and H1 is accepted. From the results of the study, it was concluded that there was a significant relationship between attention to parenting patterns and the learning independence of fifth grade students at SD Gugus III, Majuleng District, Wajo Regency.